Pengaruh Kecepatan Putaran dan Pemakanan terhadap Permukaan Baja ST 41 pada Mesin Bubut - Akhmadi, Amin Nur; Usman, Mukhamad Khumaidi; Sanjaya, Firman Lukman (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2024)
This study discusses the effect of feed rate and machine rotation speed on the surface roughness of ST 41 steel in the flat turning process. The aim is to determine the relationship between variations in rotation speed (100 rpm, 300 rpm, and 500 rpm) and feed rate on the final surface results of the workpiece. The method involves cutting tests on ST 41 steel specimens with a diameter of 25 mm and a length of 400 mm with various rotation speed variations. The results show that at low rotation speed (100 rpm), the surface of the workpiece tends to be rough. The surface becomes better at medium speed (300 rpm), while at high speed (500 rpm), the surface results are smoother. These findings indicate that increasing rotation speed contributes to a decrease in surface roughness. Thus, higher rotation speeds can improve the quality of turning results.